A new polyoxygenated cyclohexene derivative from Artabotrys hainanensis. Issue 14 (18th July 2018) - Tang, Jin-Ying; Liu, Yan-Ping; Ju, Peng-Kun; Luo, Xiu-Lan; Zhang, Zhi-Jie; Ren, Peng; Lai, Liang; Chen, Guang-Ying; Fu, Yan-Hui
Abstract: A new polyoxygenated cyclohexene derivative, artahainanol A (1 ), together with three known analogues (2 –4 ), was isolated from the stems and leaves of Artabotrys hainanensis . Among them, 1 is an unusual polyoxygenated cyclohexene containing 14 carbon atoms on the carbon skeleton. All known compounds (2 –4 ) were isolated from the genus Artabotrys for the first time. The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in the literature. All isolated compounds were evaluated for their cytotoxicities against five human cancer cell lines: HL-60, SMMC-7721, A-549, MCF-7 and SW480 in vitro . Compounds1 –4 showed significant inhibitory effects against various human cancer cell lines with IC50 values ranging from 2.68 to 18.32 μM. Abstract :